First record of Sonotrella Gorochov (Orthoptera: Gryllidae) from Laos, with description of a new species - Liu, Hao-Yu; Zhang, Dong-Xiao; Shi, Fu-Ming (Zootaxa, 2016)
The genus Sonotrella Gorochov, 1988 is recorded to Laos for the first time. A new species is described and illustrated, S. (Sonotrella) laosensis sp. nov. (type locality: Laos). A distribution map of the species of Sonotrella (Sonotrella) and a key to the subgenera of Sonotrella worldwide are given.